Strategi Komunikasi Pemerintah Kota Padang Dalam Meminimalisir Infodemic Vaksinasi Covid-19 - Rahmadhona Fitri Helmi; Pratiwi Nurhabibie; Yuliarti Yuliarti; Yulia Hanoselina (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Currently, the dissemination of information looks pretty excessive in the pandemic Covid-19; it is called an infodemic. As stated by WHO Director-General Tedros Adhanom Ghebreyesus,